Stakeholder Analysis on Indonesian E-Commerce Taxation - Setiawan, Amelia; Maratno, Sylvia Fettry Elvira; Rahayu, Puji Astuti; Dewanti, Monica Paramita Ratna Putri (Universitas Prasetiya Mulya, 2019)
The growth of Indonesian online trading activities is predicted to be extremely high because of the huge number of internet users in Indonesia. This is perceived as a great chance to enter the online commercial trading market. The online marketplace makes it easy to buy and sell goods and services efficiently. However, there is little consideration on the taxation aspect of e-commerce transaction in Indonesia. This study analyzed Indonesian e-commerce taxation based on main group of stakeholders. The literature review is conducted to get comprehensive understanding on common e-commerce taxation. The analysis of e-commerce taxation grasps the comparison of practices between developed and developing countries. In order to get more depth understanding in Indonesian e-commerce taxation, questionnaires distributed to main group of stakeholders. The result has shown that the regulation applied for e-commerce transaction is considered sufficient. However, improvement on the e-commerce tax compliance of related parties must be enforced.